Disseminated Mycobacterium massiliense infection in a patient with myelodysplastic syndrome undergoing allogeneic bone marrow transplantation. Issue 3 (19th May 2020) - Toyama, Takaaki; Mori, Takehiko; Kato, Jun; Sugita, Kayoko; Hasegawa, Naoki; Nakata, Noboru; Hoshino, Yoshihiko; Okamoto, Shinichiro
Abstract: Nontuberculous mycobacteria are ubiquitous in water and soil, and the subset of rapidly growing mycobacteria species can cause severe infections in immunocompromised patients. Solid organ or hematopoietic stem cell transplantation (HSCT) recipients are known to be susceptible to infection by nontuberculous mycobacteria . The nontuberculous mycobacteria species Mycobacterium massiliense ( M massiliense ) has been classified as a rapidly growing mycobacteria and recognized as a pathogen causing lung and soft tissue infections in humans. However, there have been only a few reported cases of M massiliense infection after solid organ transplantation and HSCT. We herein report another case of M massiliense infection after allogeneic HSCT, which manifested as soft tissue infection, lung infection, and bacteremia.